Zeugitai in Fifth-Century Athens: Social and Economic Qualification from Cleisthenes to the End of the Peloponnesian War - Valdés Guía, Miriam (Pnyx: Journal of Classical Studies, 2022)
The status of zeugitai as middle-class hoplites has received considerable attention in recent decades regarding property requirements for inclusion into the hoplite rank and their expected role in the Athenian army. Accordingly, this paper re-examines the idea that since the time of Cleisthenes and throughout the fifth century, the ​​zeugitai formed a census class of middling owners with an estate equivalent to at least 3.6 hectares. It argues that late-sixth century reforms converted the property holdings of zeugitai into a monetary equivalent (in drachmas) and used the census classes as an economic criterion for recruitment from the hoplite catalogue. Already in the sixth century but especially during the Pentecontaetia, the number of hoplites/zeugitai grew substantially due to economic prosperity and the foundation of colonies and cleruchies. Many citizens without landholdings but in possession of sufficient wealth were included in the zeugitai census class and, like the famous Anthemion ([Arist.] Ath. Pol. 7.4), could ascend even higher.